O encontro-confronto com a língua inglesa em diferentes instâncias enunciativas pedagógico-educacionais - Vieira, Evelyn Cristine (2018)
This thesis aims to develop a discursive approach on certain representations about English teaching-learning process in distinct pedagogical-educational enunciative instances and it is based on utterances of teachers, professors and in-service teachers. It was designed to investigate how some teachers enunciate about the English language teaching-learning process from the following instances: regular public school, regular private school, language and federal institutes and university. In order to do so, as a theoretical-methodological support, it was developed an inter/transdisciplinary approach that involves Applied Linguistics (AL), French Discourse Analysis (FDA) and Bakhtin Circle studies. For the data collection, we based on the AREDA proposal, by Serrani- Infante (1998) in which ten teachers, who participated in the research, enunciated. When analyzing how these participants built the representations of such process we found three axes that guided the organization of some representations related to the learning process, to the pre-service education and to the in-service practice. In each one of the axes, the main discursive inscriptions of the teachers were discussed when they enunciated about teaching-learning English and the encounter-confront with this language in this process. Concerning the representation of learning, the teachers affiliate themselves in the fascination and passion about the language, in the language utility and in the need to belong to the other language. Concerning education, they are inscribed in the fascination and passion about the language, in the lackness of the education process and in the theory-practice relation. Regarding their practice, teachers inscribe themselves in the English language mastery, in the (in)efficiency of teaching, and in the (de)valuation of the English language. Due to the fact we noticed that the discursive inscriptions and voices mobilized by teachers to build such representations are interconnected, we established, based on the three axes, the constitutive-dialogic relations among the representations built by the teachers. The purpose is to problematize the dialogicity found among the teachers’ utterances of the five pedagogical-educational enunciative instances through the discussion of consonant and dissonant voices in such dialogicity. We comprehend that the teachers are in continuous interpellation when representing the English teaching-learning process, which is related to experiences on discursive events and theme. The results of this study allow us to defend the English teaching-learning and teachers education processes to be discursively comprehended, always as inconclusive and unfinished processes, (re)signified by the participants, which necessarily includes taking a political position.